Ketika Krisis Siapa Bertanggung Jawab? Analisis framing Pertanggungjawaban Pertamina Terhadap Korban Kebakaran Depo Plumpang - Maharani, Indah; Ainul Jannah, Adillah; Sukmawati, Ade Irma (Jurnal Mahasiswa Komunikasi Cantrik, 2023)
In every crisis, questions almost always arise regarding the company's responsibility for victims resulting from the crisis. It also depends on how the media frames it. This research was conducted to determine the form of framing of news articles regarding Pertamina's responsibility for the victims of the Plumpang Depot fire. Analysis was carried out for news broadcasts by CNN Indonesia and Kompas.com. The framing analysis model used is Robert Entman. The news analyzed consisted of nine news stories from CNN Indonesia and ten news stories from Kompas.com. The research results found that these two media tend to present news from a point of view that is in line with the government, an aspect that is manifested through the prevalence of reporting that emphasizes clarification from accurate and trustworthy parties, especially from Pertamina's internal sources. The difference in reporting on CNN and Kompas lies in the focus of the reporting delivered. CNN focuses on Pertamina's accountability, while Kompas focuses on Pertamina's handling of victims affected by the Plumpang Depot fire.